2013
DOI: 10.1016/j.elecom.2012.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrochemistry of cytochrome bo3 oxidase at a series of gold nanoparticles-modified electrodes

Abstract: New membrane-protein based electrodes were prepared incorporating cytochrome bo3 from E. coli and gold nanoparticles. Direct electron transfer between the electrode and the immobilized enzymes was achieved, resulting in an electrocatalytic activity in presence of O2. The size of the gold nanoparticles was shown to be important and smaller particles were shown to reduce the overpotential of the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…The technique is based on porous three‐dimensional gold nanoparticle electrodes obtained by drop‐casting a concentrated gold colloid on the surface of a polycrystalline gold substrate. These electrodes allow both an exceptionally high surface coverage and a reversible direct electron transfer with the immobilized enzyme [22–24]. After immobilization of CcO, the catalytic current and the oxygen reduction potential can be investigated in presence of oxygen [23].…”
Section: Introductionmentioning
confidence: 99%
“…The technique is based on porous three‐dimensional gold nanoparticle electrodes obtained by drop‐casting a concentrated gold colloid on the surface of a polycrystalline gold substrate. These electrodes allow both an exceptionally high surface coverage and a reversible direct electron transfer with the immobilized enzyme [22–24]. After immobilization of CcO, the catalytic current and the oxygen reduction potential can be investigated in presence of oxygen [23].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, cco with a His-tag on subunit I did not show any direct electrocatalytic behavior in similar ptBLM assemblies, which again emphasizes the importance of protein orientation. We have recently shown that oxidases immobilized on 15 nm gold NPs modified with a mixture of hexane thiol and 6-mercapto-1-hexanol also exhibit a clear electrocatalytic activity in presence of oxygen, see Figure 3 (Melin et al , 2013 ). Larger NPs mediate the electron transfer less efficiently.…”
Section: Terminal Oxidasesmentioning
confidence: 99%
“…In a preliminary study, our group has shown that gold NPs constitute an efficient support for the immobilization of several respiratory membrane proteins fragments from the thermophilic bacterium Thermus thermophilus (Meyer et al , 2011 ). The immobilization of full terminal oxidases on gold NPs is now possible (Melin et al , 2013 ).…”
Section: Mixed Protein/nanomaterials Filmsmentioning
confidence: 99%
“…[328][329][330] Immobilization of these enzymes on electrodes is a challenge, however, because it requires sophisticated modification of the electrode mimic of the cell membrane. [331,332] Moreover, many of the terminal oxidases currently reported reduce oxygen at a much lower potential than MCOs. [333] Some bacterial metabolisms in the biodiversity pool are known to involve high-potential electron-transfer chains.…”
Section: Chemelectrochem Reviewsmentioning
confidence: 99%